2018
DOI: 10.1039/c8sc01288a
|View full text |Cite
|
Sign up to set email alerts
|

A bottom-up synthesis of rare-earth-hydrotalcite monolayer nanosheets toward multimode imaging and synergetic therapy

Abstract: Gd3+ and Yb3+ co-doped LDH monolayer nanosheets are developed via a facile “bottom-up” method and exhibit excellent drug loading capacity for tri-mode imaging guided cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 60 publications
(25 reference statements)
0
43
0
Order By: Relevance
“…Layered double hydroxides, which are also known as hydrotalcite‐like compounds are a class of 2D nanomaterials with chemical compositions of [M 1− x 2+ M x 3+ (OH) 2 ] x + [A x / n ] n − ·mH 2 O, where M 2+ and M 3+ are bivalent and trivalent metal cations, respectively, and A m − is an interlayer anion . The diversity in the chemical composition and crystal structure of LDHs is attributed to their vast applications in many different fields .…”
Section: Layered Double Hydroxide Nanosheetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Layered double hydroxides, which are also known as hydrotalcite‐like compounds are a class of 2D nanomaterials with chemical compositions of [M 1− x 2+ M x 3+ (OH) 2 ] x + [A x / n ] n − ·mH 2 O, where M 2+ and M 3+ are bivalent and trivalent metal cations, respectively, and A m − is an interlayer anion . The diversity in the chemical composition and crystal structure of LDHs is attributed to their vast applications in many different fields .…”
Section: Layered Double Hydroxide Nanosheetsmentioning
confidence: 99%
“…Similarly, Gd and Mn‐doped LDH nanoparticles (Gd‐LDH NPs and Mn‐LDH NPs, respectively) with superb longitudinal relaxivity have been reported as excellent contrast agents for MRI . In addition, Mei et al designed Gd‐ and Yb‐codoped LDH nanosheets for dual‐modal MR/CT imaging to overcome the limitations of singular imaging approaches . Moreover, a pioneering study of LDHs in PET imaging have been reported by Cai et al It was found that the trivalent cation 44 Sc 3+ and the bivalent cation 64 Cu 2+ could be used to successfully label BSA‐LDHs with a good labeling stability and efficiency (Figure B) .…”
Section: Layered Double Hydroxide Nanosheetsmentioning
confidence: 99%
“…As a class of 2D nanomaterials, LDHs have been widely explored as inorganic-biology composite materials for biomedical applications, owning to their good stability, excellent biocompatibility and the versatility in chemical composition [99][100][101]. Typically, LDHs are composed of a layer of metal atoms sandwiched between hydroxide layers, possessing a high layer charge density, which can realize chemical modifications or interlayer composition changes [102].…”
Section: Ldhs For Biomedical Applicationsmentioning
confidence: 99%
“…In addition, due to the tunable composition of host layers, specific imaging functions can be achieved via changing the metal elements of layers. In a recent report by Mei et al [101], rare-earth (Gd 3+ and Yb 3+ ) co-doped LDH single-layer nanosheets (Gd&Yb-MLDH) were prepared by one-step ''bottom-up" method, showing a uniform morphology. With the successful introduction of Gd 3+ and Yb 3+ into the host layer of LDH, the Gd&Yb-MLDH single-layer nanosheets exhibited superior magnetic resonance (MR)/computed tomography (CT) dual-mode imaging performance.…”
Section: Ldhs For Biomedical Applicationsmentioning
confidence: 99%
“…In vivo efficacy study demonstrated that almost complete ablation of the tumor was achieved by ZnPc/LDH at a low dosage of ZnPc (Figure b,c) . Based on the principle, more sophisticated systems developed by Wei and co‐workers include Ce6 and AuNPs‐loaded Gd‐incorporated LDH for MR/fluorescence dual‐mode imaging‐guided PDT (Figure d), and rare‐earth (Gd 3+ and Yb 3+ )‐doped, SN38 and indocyanine green (ICG)‐delivered LDH for CT/MR/fluorescence trimode imaging‐guided PDT‐included combination therapy …”
Section: Smart Ldh For Theranostic Nanomedicinementioning
confidence: 99%